Pendidikan Kesehatan Tentang Bahaya Penyakit Demam Berdarah Dengue (DBD) Pada Masyarakat - Vierto Irennius Girsang; Laura Mariati Siregar; Asima Sirait (Lembaga Penelitian dan Pengabdian Masyarakat STIE Eka Prasetya, 2024)
Dengue Fever disease is a disease whose sufferers tend to increase. Dengue fever disease is an illness that is heard by Dengue virus. Increased cases of dengue high fever can be influenced by the population density factor. The population density factor affects the transmission or transfer of disease from one person to another associated with a vector of disease. This community service activity was carried out in the PB Selayang II Community Health Center Work Area on 18-19 June 2024. The health education media used were videos and leaflets. The implementation is carried out during the day for people who can come during the day. The average number of people attending is ten to twenty people. Health education about the dangers of dengue hemorrhagic fever was carried out in three sessions. After carrying out community service activities, it can be concluded that there has been an increase in public knowledge about the dangers of dengue hemorrhagic fever before and after this activity. After conducting health education, the public understands more about the dangers of dengue hemorrhagic fever.